Belgium : 2020 Article IV Consultation-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for Belgium. (IMF Staff Country Reports; Country Report ;, 2020)
This 2020 Article IV Consultation with Belgium highlights that economic activity has held up relatively well over the last year, but the outlook is clouded by unusual uncertainty and risks. The coronavirus outbreak is expected to reduce growth this year, and the outlook is highly uncertain and subject to risks, including more widespread and damaging effects of the coronavirus, escalating trade tensions, a sharper euro-area growth slowdown, and prolonged domestic political gridlock. Policies should focus on addressing the coronavirus outbreak in the near term and rebuilding resilience and addressing structural challenges in the medium run. The immediate policy priority is to contain the spread and damaging effects of the coronavirus through targeted temporary support measures to affected firms and individuals, while ensuring that the healthcare system has adequate resources to address the crisis. Reversing the declining trend in productivity growth is essential to support higher standards of living and safeguard fiscal sustainability. Thus, reform efforts would need to focus on reducing red tape for start-ups, lowering regulatory barriers to competition in key sectors, supporting access to venture capital for innovative firms, and boosting public investment in infrastructure, fiscal space permitting.